Online marketingová komunikace cílící na děti školního věku - Burešová, Jitka (Masaryk University Press, 2023)
Title in English: Online marketing communication targeting school-age children The online environment contains many forms of marketing messages, many of which cannot be easily distinguished from regular content. Due to their lack of experience, children are more susceptible to marketing messages that influence their buying habits. The respondents in our research were children between the ages of 10 and 13, who are both consumers and customers and who play an important role in the purchasing decisions of their families. Investigating the types of online marketing communications children consume, their attitudes towards them and whether and how this influences their purchasing is therefore of paramount importance. We conclude with practical recommendations for schools and parents on how to educate children about online marketing.